City liveability and housing in Nigeria: a case study of low-income housing in Niger State - Mohit, Mohammad Abdul; Sule, Abass Iyanda (2015)
Studies on the liveability of cities have been on the increase due to their perceived aftermath significant contributions to the quality of life. Although the quality of life (QOL) has been studied from different disciplines, however, it does not mean absence of diseases or sickness rather QOL depends primarily on the living environment. The aim of this study is to examine the quality of life against the backdrop of the existing environment in the public low-income housing estates in Niger State of Nigeria. The conceptual framework for this study was developed based on empirical review. Based on the desktop literature the study used both subjective and objective measurements to investigate the liveability of the selected housing estates. Issues examined include the home environment, neighbourhood amenities,economic vitality, social environment and civic protection. Questionnaires were distributed to household heads in the selected three housing estates. The stratified random sampling technique used was to choose all types of homes. The data analysis techniques include; descriptive statistics, factor analysis and structural equation modelling (SEM). This study contributes to the existing body of knowledge in liveability studies in terms of model construct. It also uncovers the quality of life in public low-income housing in Niger State.